2021
DOI: 10.1111/aos.14872
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus PCR in 2230 explanted corneal buttons

Abstract: Purpose To determine herpes simplex virus (HSV) DNA prevalence and mean cycle threshold of polymerase chain reaction (PCR) in corneal tissue of patients with penetrating keratoplasty (PKP), with (HSK+) and without (HSK−) previous clinical herpetic keratitis history. Methods Retrospective review of recipient corneal buttons which were explanted through PKP between March 2010 and September 2018 at the Department of Ophthalmology, Saarland University Medical Center in Homburg/Saar, Germany. Corneal tissue samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 27 publications
3
25
0
4
Order By: Relevance
“…However, our findings are similar to those reported in an earlier survey in Germany, whereby younger age was found to be associated with a negative attitude toward corneal donation and a positive attitude was correlated with increasing age, which may be explained by the fact that compared with young people, older individuals have had a greater opportunity to reflect on their deaths (20). In particular, we found that people with higher education levels were more willing to donate, which is consistent with many previous reports from other countries and the north of China (17,21,22). A higher education level might lead to a better understanding of (1999-2003, 2004-2008, 2009-2013, and 2014-2018).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, our findings are similar to those reported in an earlier survey in Germany, whereby younger age was found to be associated with a negative attitude toward corneal donation and a positive attitude was correlated with increasing age, which may be explained by the fact that compared with young people, older individuals have had a greater opportunity to reflect on their deaths (20). In particular, we found that people with higher education levels were more willing to donate, which is consistent with many previous reports from other countries and the north of China (17,21,22). A higher education level might lead to a better understanding of (1999-2003, 2004-2008, 2009-2013, and 2014-2018).…”
Section: Discussionsupporting
confidence: 91%
“…htm), were more willing to donate corneas compared to other counties, suggesting that economic development may influence corneal donation. This result is in line with reports showing that lower economic levels are a practical obstacle to corneal donation (21,23). Among participants of different socioeconomic sectors, employees working in medical sectors have a relatively lower willingness to donate their corneas than employees working in non-medical settings (20).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…), the DMEK donor is marked during harvesting with 3 asymmetric semicircles at the margin according to Bachmann, Cursiefen, and Kruse, in order to be able to determine unequivocal graft orientation in the anterior chamber [15]. ▪ The removed Descemet membrane containing the inferior endothelial cells is always sent to virology along with an aqueous humor aspirate for viral PCR (HSV, VZV, CME, and EBV) [11]. ▪ Care is taken to center the DMEK graft as well as possible within the PKP graft.…”
Section: Dsaek Vs Dmek After Pkpmentioning
confidence: 99%
“…Ursache des Transplantatversagens nach PKP sind häufig eine endotheliale Immunreaktion 5 , 6 , ein chronisch nicht regulierter Augeninnendruck, insbesondere bei der Grunderkrankung Buphthalmus 7 , transplantierte Guttae aus der Hornhautbank bei bis zu 15% aller PKPs 8 , 9 , eine herpetische Endotheliitis als Reaktivierung einer vorbestehenden, schlummernden Herpesinfektion im Bereich der Wirtshornhaut oder aufgrund einer transplantierten Herpesinfektion, die sich im Extremfall auch als Hornhautulkus manifestieren kann 10 , 11 . Insbesondere bei vorbestehender pseudophaker bullöser Keratopathie als Ursache für die Keratoplastik kann nach vielen Jahren – auch ohne akutes Ereignis – eine chronische Transplantatermüdung auftreten.…”
Section: Introductionunclassified